Potensi Ekstrak Daun Carica Pubescens Sebagai Alternatif Antidiare Bakteri Vibrio cholerae dan Shigella dysentriae - Astuti, Tri Dyah; Hadi, Wahid Syamsul (Jurnal Teknologi Laboratorium, 2018)
Acute diarrhea is one of the main causes of morbidity and mortality. A people are starting to choose traditional medicines for alternative therapy. Traditional medicines or herbal medicines are considered safer and do not have side effects such as chemical drugs. The purpose of this study was to determine the anti-diarrhea effect of Carica pubescens leaf extract on the bacteria Vibrio cholerae and Shigella dysentriae. This study was conducted by testing the activity of Vibrio cholerae and Shigella dysentriae bacteria on Carica pubescens leaf extract with a well method, which results can be seen from the formation of inhibitory zones. The data obtained were processed using Two Way ANOVA test statistics. The results showed that the leaves extract of Carica Pubescens concentration of 100% had the best therapeutic effect because it had the greatest inhibitory power on the bacteria Vibrio cholerae and Shigella dysentriae.